Immediate effect of physical activity on gut motility in healthy adults - Kento Katagiri; Soichiro Koyama; Kotaro Takeda; Kouji Yamada; Koki Tan; Hikaru Kondo; Yohei Otaka; Shigeo Tanabe (Scientific Reports, 2025)
Abstract Constipation is a prevalent condition that negatively impacts health and quality of life. Inadequate physical activity is a known contributing factor, often associated with reduced gut motility. However, the physiological mechanism linking physical activity and constipation remains unclear. Particularly research on the immediate effects of physical activity on peristalsis is scarce. Therefore, we aimed to elucidate this mechanism by examining the immediate effects of physical activity on gut motility in healthy adults. Twenty-one participants were instructed to walk on a treadmill for 20 min. Bowel sounds were assessed at rest and at intervals up to 15 min after walking. Bowel sounds were used as indirect markers of gut motility. We calculated the sum of the absolute signal amplitudes of bowel sounds, the percentage of bowel sounds duration, and number of discrete bowel sounds, which have been proposed as indices of gut motility. All the indices increased significantly 1–2 min post-exercise compared to resting values. This increase may be attributed to changes in the autonomic nervous system and local reflexes caused by biomechanical oscillations. In addition, gut motility activation might explain the effects of physical activity intervention on constipation and offer insights into its potential role in managing the condition.